The Production and Use of Monoclonal Antibodies for the Detection of Avian Influenza Antigen in the in Infected Chickens - Astawa, Nyoman Mantik; Suardana, Ida Bagus Kade; Kencana, Gusti Ayu Yuniati (Jurnal Veteriner, 2013)
A safe and appropriate diagnostic method for avian influenza virus (AIV) infection in chickens wasestablished using monoclonal antibodies (mAbs) against the virus. The virus used for the production of themonoclonal antibodies was an Indonesian AIV-H5N1 isolate. Immortal mouse myeloma cells were fusedwith the lymphocytes derived from the spleen of mice immunized with the virus. The mAbs were tested fortheir specificity by enzyme linked immunosorbent assay (ELISA) and western blotting using formaldehydeinactivated virus and normal allantoic fluid as antigens. Twelve mAbs specific against AIV were isolatedand 8 mAbs were used for immunodetection of AIV antigen in chicken’s tissues. By indirect ELISA, themAbs were able to detect AIV antigen in allantoic fluid at the titre as low as 2-2 to 2-4 HA units per 0.1 ml.By immunoperoxidase staining AIV–antigen was detected in paraffin embedded tissues of AIV-infectedchickens. AIV antigen was not detected in chickens which were confirmed to be AIV negative. In theinfected chickens, high intensity of AIV antigen was detected in proventricle gland and small intestine.The AIV antigen with a lesser intensity was detected in lungs and spleen but hardly detected in muscle,brain and several other tissues. This study show clear evidences that mAbs produced in this study areapplicable for use in the detection of AIV antigen in infected chickens.
Keywords: avian influenza, H5N1, monoclonal antibodies, chickens, virus immunoperoxidase.